2016
DOI: 10.5535/arm.2016.40.5.845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plantar Flexor Muscle Static Stretching Alone and Combined With Massage on Postural Balance

Abstract: ObjectiveTo evaluate and compare the effects of stretching and combined therapy (stretching and massage) on postural balance in people aged 50 to 65 years.MethodsTwenty-three subjects participated in this nonrandomized clinical trial study. Each participant randomly received plantar flexor muscle stretching (3 cycles of 45 seconds with a 30-second recovery period between cycles) alone and in combination with deep stroking massage (an interval of at least 30 minutes separated the two interventions). The data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…The present results are partially in line with previous investigations, in which an overall worsening in BC after PS was reported [ 3 , 8 , 9 ]. In particular, an increase in postural sway accompanied by an increase in gastrocnemius lateralis activation was previously reported [ 3 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present results are partially in line with previous investigations, in which an overall worsening in BC after PS was reported [ 3 , 8 , 9 ]. In particular, an increase in postural sway accompanied by an increase in gastrocnemius lateralis activation was previously reported [ 3 ].…”
Section: Discussionsupporting
confidence: 94%
“…Particularly, an alteration in the afferent feedback coming from the proprioceptors of the stretched muscle has been advocated as a possible mechanism underlying the PS-induced reduction in muscle force-generating capacity [4,5]. Interestingly, these mechanical and neuromuscular factors may also affect BC [3,8,9], even though the literature on this subject is controversial. Indeed, improvements [10][11][12], worsening [3,8,9], or no changes [10] in BC were reported after PS.…”
Section: Introductionmentioning
confidence: 99%
“…However, our results do relate to findings from different authors on the acute effects of static stretching. Such studies reported a significant decrease in postural control after static stretching of calf muscles [23,24,35] which could also be related to deterioration of ankle force sense, and may consequently impair balance control with ankle strategy. Reduced ankle force sense acuity can be also explained as being caused by reduced muscle power output and muscle force after static stretching [36,37] thus affecting force sense perception.…”
Section: Discussionmentioning
confidence: 99%
“…These changes could be due to mechanical adaptations of muscle-tendon unit and adjustments in the neural system. Static stretching may also cause peripheral changes such as reduced passive MTU stiffness and increased MTU length [24] which affects muscle spindle receptors and Golgi tendon organs. Changes at the neural level are associated with decreased afferent input into the motor neuron pool, and therefore on reduced tonic reflex activity [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation